A Solitary Fibrous Tumor of the Pleura Revealed by Hiccups - A. Chafik; M. Alaoui; A. Benjelloune; Y. Qamouss (Case Reports in Medicine)
Solitary fibrous tumors of the pleura are rare and benign primary localized tumors; they possess a malignant potential and thus should be excised. We report a case of a 43-year-old woman, who had suffered for 5 years from right basithoracic pain associated with progressive dyspnea and persistent hiccups during the last 6 months. We have not found any similar case in the literature. Further testing after excision by thoracotomy revealed a solitary fibrous pleural tumor. A brief discussion of the clinical presentation and incidence of these tumors is included.